HUBUNGAN ANTARA KOMITMEN AFEKTIF DENGAN KOMPETENSI ORIENTASI LAYANAN PELANGGAN (CUSTOMER SERVICE ORIENTATION) - Mujiasih, Endah (Faculty of Psychology, Diponegoro University, 2016)
Affective commitment or emotional self-involvement in the organization was the willingness of employees to do their best for the organization benefit. The purpose of this study was to determine the relationship between affective commitment with customer service orientation. The population in this study were employees of Company